The case of the girl in grey - Stratford, Jordan (Stratford, Jordan. Wollstonecraft Detective Agency, 2017)
The young Lady Ada Byron and Mary Godwin, best friends and founders of the now popular Wollstonecraft Detective Agency, brave a ghostly girl, a creepy crypt, and a deadly storm to unlock the secrets of Dedlock Hall in their next case.